A randomized, double-blind, placebo-controlled, multicenter trial- DL-3-n-butylphthalide therapy for cerebral hypoperfusion from unilateral internal carotid system stenosis study: study protocol - Chen, Dawei; Yin, Yanwei; Shi, Jin; Ma, Xiaoxuan; Shi, Huiping; Huang, Feng; Qiu, Feng; Tang, Yonghong (International Journal of Clinical Trials, 2023)
Background: Cerebral hypoperfusion caused by large-vessel stenosis is an important risk factor for ischemic stroke and vascular cognitive impairment. In vitro, animal and clinic studies demonstrated that DL-3-n-butylphthalide (NBP) can improve the collateral circulation and the cerebral perfusion. In this trial, the benefit of NBP to ameliorate the chronic cerebral hypoperfusion resulting from unilateral internal carotid system stenosis will be explored. Methods: This trial is a randomized, double-blind, placebo-controlled, multicenter clinical study. A total 480 subjects with ≥70% stenosis or occlusion in unilateral internal carotid artery system, cerebral hypoperfusion in the ipsilateral middle cerebral artery (MCA) territory, and no transient ischemic attacks (TIA) or ischemic strokes within 2 weeks will be enrolled in China. Patients will be assigned in a 1:1 ratio to NBP and placebo groups. Patients in NBP or placebo group received 200 mg or 20 mg of NBP capsules three times daily for 4 weeks respectively. The cerebral perfusion will be assessed again after 12 weeks. The primary efficacy outcome is the proportion of patients with cerebral blood flow (CBF) amelioration, stabilization and deterioration after treatment. Conclusions: This trial will provide a high-level of evidence for NBP to treat the cerebral hypoperfusion, and a novel strategy to improve the cerebral hemodynamic impairment due to large intracranial and extracranial atherosclerotic stenosis in the surgical high-risk patients, especially in the aged and Asians. Trial registration: This trial is registered as ChiCTR2100053112 on November 12th, 2021.